Mapping the Evolution of Tourism Studies in Bali: A Comprehensive Network Analysis - Ramang H. Demolingo; Putu Pramania Adnyana; Titus Indrajaya; M.A. Inez Saptenno (Pusat Kajian Bali Universitas Udayana, 2024)
This study aims to comprehensively review Bali tourism-related literature from 1979 to 2022. The research employed a mixed-methods approach, combining bibliometric techniques and a literature review. The analysis includes 128 international publication records from the Scopus database that contain the keywords